Understanding the impacts of emerging infectious disease (EID) media exposure: the case of U.S. Ebola virus disease (EVD). - Mason, A. M.; Wright, Kevin B.; Lambert, Laura (Journal of Communication in Healthcare, 2021)
Using the Extended Parallel Processing Model (EPPM) as a theoretical framework this study examines the impact of Ebola virus disease (EVD) media exposure on U.S. audience perceptions of the threat severity, personal susceptibility, and behavioral intentions to respond to the 2014 Ebola virus disease (EVD) threat. Respondents included (n = 255) residents from the Midwest and Southern regions of U.S. Participants completed an online survey between 28 October and 3 December 2014 during the height of Ebola-related media coverage. Findings reveal that increased exposure to EVD media content was associated with increased threat severity and personal susceptibility. According to the EPPM this is a prerequisite to engaging in either fear control or danger control processes. Increased consumption of Ebola-related media content was found to increase the audience willingness to engage in protective behaviors. These findings support the position that increased exposure to EVD media content motivated individuals to engage in danger control, opposed to fear control processes (Roberto AJ, Goodall CE, Witte K. Raising the alarm and calming fears: perceived threat and efficacy during risk and crisis. In: Handbook of risk and crisis communication; 2010). This study offers a number of implications in terms of better understanding audience reactions to EID cases and practical implications for health campaign practitioners. Early-stage risk communication about emerging infectious disease (EID) threats need to focus on building and maintaining trust, addressing knowledge gaps, and developing reasonable understandings of threat severity and public susceptibility.